2005
DOI: 10.1124/mol.104.008086
|View full text |Cite
|
Sign up to set email alerts
|

A Natural CYP2B6 TATA Box Polymorphism (–82T→ C) Leading to Enhanced Transcription and Relocation of the Transcriptional Start Site

Abstract: We investigated the impact of promoter polymorphisms on transcription of the human CYP2B6 gene. In total, 98 DNA samples from white persons from a previously characterized liver bank were sequenced throughout 2.3 kilobases of upstream sequence and haplotype structures were determined using additional coding sequence information. HepG2 cells and primary rat and human hepatocytes were transfected with luciferase reporter gene constructs driven by 2033 base pairs (bp) of the most frequent promoter variants. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 37 publications
5
85
0
1
Order By: Relevance
“…reaction assay with predesigned primers and TaqMan MGB probes (TaqMan SNP Genotyping Assay; Applied Biosystems, Foster City, CA) or previously published primers and MGB probes (Tsuchiya et al, 2004;Klein et al, 2005;Zukunft et al, 2005;Gatanaga et al, 2007) using the ABI PRISM 7900HT Real-Time PCR System (Applied Biosystems). All PCR reactions were performed in a 25-l volume containing 20 ng of genomic DNA, 2ϫ TaqMan Universal master mix (Applied Biosystems), and 20ϫ drug metabolism genotyping assay mix (Applied Biosystems) or 40ϫ assay mix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…reaction assay with predesigned primers and TaqMan MGB probes (TaqMan SNP Genotyping Assay; Applied Biosystems, Foster City, CA) or previously published primers and MGB probes (Tsuchiya et al, 2004;Klein et al, 2005;Zukunft et al, 2005;Gatanaga et al, 2007) using the ABI PRISM 7900HT Real-Time PCR System (Applied Biosystems). All PCR reactions were performed in a 25-l volume containing 20 ng of genomic DNA, 2ϫ TaqMan Universal master mix (Applied Biosystems), and 20ϫ drug metabolism genotyping assay mix (Applied Biosystems) or 40ϫ assay mix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Lower expression was also found in cell lines transfected with *6, *11, *12, *13, *14, *15, *16, *18, *19, *20, and *21 alleles (Lang et al, 2004;Klein et al, 2005;Wang et al, 2006;Hofmann et al, 2008). Higher expression was detected *22-transfected cells (Zukunft et al, 2005). The *27 allele was reported to result in decreased in vitro enzymatic activity of bupropion hydroxylase, and *28 was reported to result in truncated protein (Rotger et al, 2007).…”
mentioning
confidence: 92%
“…The thermal cycling conditions for the assay were 2 min at 50°C, 10 min at 95°C, followed by 40 cycles of 15 s at 95°C and 1 min at 60°C. Previously published TaqMan assays were used for the mRNA quantification of CYP2B6 (Zukunft et al, 2005), CYP2C19 (Burk et al, 2005), CYP2D6 (Toscano et al, 2006), and CYP3A4 Wolbold et al, 2003). All primers and probes used are presented in Table 2.…”
Section: P450 Activity Assays and Cocktail Assay Development Lc-ms/mmentioning
confidence: 99%
“…In contrast to the above-mentioned CYP genes, variations in CYP2B6 have been discovered through reverse genetics studies, i.e., by initial sequencing and variation scanning studies and subsequent analysis of the functional consequences of the identified variations (17)(18)(19)(20)(21)(22)(23)(24)(25). More than 100 DNA variations, including numerous nonsynonymous variations, as well as silent, promoter, and intronic changes, were found within the CYP2B6 gene, many of them showing extensive linkage disequilibrium giving rise to distinct haplotypes (26 ) (17,19,21,23 ), and alleles with increased expression [CYP2B6*22; (24 )]. Some of these variations are rare, but many are common, with allele frequencies between 10% and almost 50%, depending on the population studied (22,23 ).…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 99%